Off-Label Use of Intravenous Immunoglobulin with Methylprednisolone to Treat Parsonage–Turner Syndrome in a United States Marine - Carissa M. Sedlacek; Michael Leone; Adam D. Foster; Amy Hinkelman (Case Reports in Medicine)
Neuralgic amyotrophy (NA) also known as Parsonage–Turner syndrome is an inflammatory disorder of the brachial plexus characterized by sudden, acute onset of severe pain of the arm and/or shoulder followed by muscle weakness and sensory abnormalities. Although management may involve physical therapy, immunomodulatory drugs, and analgesics, there is nothing specific for the treatment of NA. Full functional recovery can take months to years, but recurrence and/or persistence of symptoms and disability are frequent. This case reports a 22-year-old male who recovered from NA within 3 months following treatment with 1000 mg of methylprednisolone and off-label use of 0.5 g/kg of intravenous immunoglobulins (IVIG) for four consecutive days. Three years later, the patient experienced soreness and paresthesia of the shoulder following a military shooting exercise, and 0.75 g/kg of IVIG and 1000 mg of MP were prescribed for 2 consecutive days resulting in complete recovery and no recurrences to date. EMG findings, 3.5-year postinitial treatment, revealed improvement in the brachial plexopathy. This provides support for the combined use of IVIG and glucocorticoids in the treatment of NA and highlights the need for further studies investigating whether this combined treatment regimen may accelerate recovery and improve long-term outcomes for patients diagnosed with NA.